NON POPULAR PRACTISES OF STHANIK CHIKITSA IN DIFFERENT GYNAECOLOGICAL DISORDERS (AYUSHDHARA, 2021)
Women health is always at risk due to her socio economic secondary status in Indian society. External opening of her reproductive system is surrounded by the infection prone zones like anal and urethral openings. Also her involvement in reproductive and sexual acts leads to many infectious disease. This entire course along with many anatomical deformities results in various pathophysiological conditions of reproductive system affecting her health. Such conditions are called as Yonivyapad i.e. diseases of female reproductive system in Ayurved texts. Puberty, menarche, sexually active and reproductive period, antenatal period, perpurium, use of various contraceptive aids, menopausal time and various gynaecological diseases are common events of her life. Twenty Yonivyapada are described by all major Ayurved Sanhita. Causes for many of them are local factors and rest are due to complications of major systemic illness. Doshas are major causative factor in yonivyapada. Various local remedies called as Sthanik Chikitsa are available which can give relief at most extent in certain Yonivyapda. Local modalities like Basti, Uttarbasti, Varti, Kalka Dharan, Kshar Pratisaran, Yoni Dhupan, Sek, Abhyang, Pichu, and Yonidhavan are much effective than any modern remedies. But these therapies are practised at institutional levels only. They are not even popular in upcoming generation of Ayurved practitioners. Promotion of these therapies at small set ups is essential to establish good clinical outcome in the management of gynaecological disorders by Ayurved therapy. Their simple techniques, importance, efficacy and cost effectiveness are more favourable aspects to implement them conveniently. Wide use and large scale acceptance can result into implementation of Sthanic chikitsa in the government public health centres in future.